Modification of hand muscle strength training equipment: study of the development of a ball stick for handball shooting - Yogi, Yogi; Perdana, Rahmat Putra; Suptiatna, Eka; HaÃ¯dara, Youssouf (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. This study aims to modify the ball stick as a hand muscle strength training aid for shooting handball as a training aid that can be used to train hand muscle strength against shooting strength.Material and Methods. The research method used is Research and Development (R&D) with the Borg & Gall Development Model. This research was conducted in several steps, namely: potentials and problems, data collection, product design, design validation, design revision, trial use. The development of modifications to hand muscle strength training tools for shooting handball was first validated by material experts, expert practitioners, 7 product trial respondents, and 15 product use trial respondents.Results. The results of this study indicate that the development of modified hand muscle strength training tools for shooting handball sports can be seen from material experts (78.75% in the appropriate category) and expert practitioners (78.09% in the appropriate category), 75.82% in small-scale trials in the appropriate category, and 82.46% in large-scale trials. eligible category. Thus, it can be concluded that the development of modified hand muscle strength training tools for shooting handball sports is declared feasible to be used as an exercise aid.Conclusions.The results of this study also provide a new reference for hand muscle strength training tools for shooting in handball sports and can be used by sports practitioners and sports coaches in providing exercise programs.